Analysis of Business Innovation Strategy and Product Differentiation Strategy in Increasing Sales Volume in Coffee Shop Msme in Sukabumi City - Meiranti Maudi; Erry Sunarya; Faizal Mulia (Jurnal Multidisiplin Sahombu, 2025)
Micro, small, and medium-sized coffee shops (MSME) in Sukabumi City face increasingly intense competition, necessitating effective business strategies to boost sales volume. This study examines the effects of business innovation strategies and product differentiation strategies on the sales volume of MSME coffee shops in Sukabumi City. A descriptive-associative method with a quantitative approach was employed; the sample comprised 114 MSME owners selected via saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed with validity and reliability tests, classical assumption tests, multiple linear regression, and F and t tests using SPSS. The results indicate that both business innovation and product differentiation strategies have positive and significant effects on sales volume. The regression analysis yielded a coefficient of determination (R²) of 0.517, meaning that 51.7% of the variation in sales volume is explained by these two variables, while the remaining 48.3% is attributable to other factors outside this study. These findings underscore the importance of implementing innovations in processes, products, and organization, as well as creating differentiation in products, services, and brand image to enhance competitiveness and sales of MSME coffee shops in Sukabumi City.